2021
DOI: 10.1039/d1fo00155h
|View full text |Cite
|
Sign up to set email alerts
|

Naringenin prevents TNF-α-induced gut-vascular barrier disruption associated with inhibiting the NF-κB-mediated MLCK/p-MLC and NLRP3 pathways

Abstract: The microvasculature endothelium accurately regulates the passage of molecules across the gut-vascular barrier (GVB), which plays an essential role in the intestinal immunity. Naringenin is with reported therapeutic potential against...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 55 publications
0
22
0
Order By: Relevance
“…The NF-κB and MAPK signaling pathways are well known to be involved in inflammation and immune regulation [40]. NF-κB is a nuclear transcription factor in cells and regulates the inflammatory response by modulating the transcription of inflammatory genes [18]. In an inflammatory environment, NF-κB p65 is phosphorylated and translocated into the nucleus, thereby promoting the transcription of inflammatory markers and inducing irreversible inflammatory injury, which is the important mechanism for regulating inflammatory diseases [31,32,41].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The NF-κB and MAPK signaling pathways are well known to be involved in inflammation and immune regulation [40]. NF-κB is a nuclear transcription factor in cells and regulates the inflammatory response by modulating the transcription of inflammatory genes [18]. In an inflammatory environment, NF-κB p65 is phosphorylated and translocated into the nucleus, thereby promoting the transcription of inflammatory markers and inducing irreversible inflammatory injury, which is the important mechanism for regulating inflammatory diseases [31,32,41].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, intestinal epithelial barrier dysfunction is related to the progression of intestinal inflammation. Increasing evidence has indicated that the activation of NLRP3 inflammasome was essential for the pathogenesis of intestinal inflammation and intestinal epithelial barrier dysfunction [18,19]. The NLRP3 inflammasome is a vital part of the innate immune system and is composed of NLRP3, caspase-1 and apoptosis-associated speck-like protein containing CARD (ASC).…”
Section: Introductionmentioning
confidence: 99%
“…TNF-α is an additional pro-inflammatory cytokine that has been implicated in IBD and causes increased intestinal epithelial TJ permeability ( 40 , 95 , 96 ). The TNF-α-induced increase in intestinal TJ permeability was also dependent on NF-κB p50/p65 activation ( 40 , 97 103 ). However, important differences are noted concerning how the enterocyte NF-κB p50/p65 was activated and how the TJ barrier was regulated.…”
Section: Mechanisms Of the Il-1β-induced Modulation Of The Intestinal Tj Barriermentioning
confidence: 99%
“…Recently, a growing body of evidence has demonstrated that the pharmacological agents, e.g., Ezetimibe ketone, Desfluoro-ezetimibe, NK-252, Bardoxolone, and TBHQ could induce activation of NRF2 ( 58 61 ). Here we proposed naringenin, a citrus flavonoid shown to have cytotoxic and antiproliferative effects on various cancer cell types ( 62 ) and regulates immunological pathways ( 63 ), to be another kind of potential NRF2 conditioning agent. With the development of immunotherapies such as cancer vaccine, immune checkpoint inhibitors, oncolytic virus, and chimeric antigen receptor T cell (CAR-T) therapy ( 64 ), a combination of NRF2-targeting agonists and immunotherapies may provide multiple feasible approaches to new BC treatment strategies.…”
Section: Discussionmentioning
confidence: 99%